2006
DOI: 10.1080/13691050500391489
|View full text |Cite
|
Sign up to set email alerts
|

HIV/AIDS and ‘othering’ in South Africa: The blame goes on

Abstract: In order to explore the relevance of social concepts such as stigma and denial to the transmission of HIV, this qualitative study sought to examine cultural and racial contexts of behaviour relevant to the risk of HIV infection among South Africans. A cultural model was used to analyse transcripts from 39 focus group discussions and 28 key informant interviews. Results reveal how cultural and racial positionings mediate perceptions of the groups considered to be responsible and thus vulnerable to HIV infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
107
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(111 citation statements)
references
References 11 publications
3
107
1
Order By: Relevance
“…First, my finding of a Tanzanian cultural context of HIV stigma and discrimination is consistent with findings of a high prevalence of HIV stigma and discrimination in African communities (e.g., Petros et al, 2006;Airhihenbuwa et al, 2009;Okoror et al, 2014). For example, drawing on a focus group study of women living with HIV/AIDS in South Africa to explore the experience of stigma in healthcare settings, Okoror et al (2014) found stigmatizing practices such as specific file colors being used for HIV-positive patients and sections of the healthcare setting reserved only for PLWHA.…”
Section: Discussionsupporting
confidence: 75%
“…First, my finding of a Tanzanian cultural context of HIV stigma and discrimination is consistent with findings of a high prevalence of HIV stigma and discrimination in African communities (e.g., Petros et al, 2006;Airhihenbuwa et al, 2009;Okoror et al, 2014). For example, drawing on a focus group study of women living with HIV/AIDS in South Africa to explore the experience of stigma in healthcare settings, Okoror et al (2014) found stigmatizing practices such as specific file colors being used for HIV-positive patients and sections of the healthcare setting reserved only for PLWHA.…”
Section: Discussionsupporting
confidence: 75%
“…This is an interesting association given that only a small percentage of participants stated that being sick was their reason for their last HIV test. The association between testing and believing that others test when they are sick, although participants themselves do not report testing because of illness, this may reflect a sense among those who have tested that they tested for the ''right'' reasons while ''others'' wait until disease progression to test (Petros et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…So much concern and alarm have been raised about the burden of HIV and AIDS related stigma and the negative impact it has on prevention [20][21][22]. As the HIV and AIDS epidemic continues to escalate in sub-Saharan Africa, the care of PLWHAs can place a significant burden on family caregivers [23].…”
Section: Introductionmentioning
confidence: 99%